2021
DOI: 10.7759/cureus.13893
|View full text |Cite
|
Sign up to set email alerts
|

Physeal-Sparing Rigid Intramedullary Nailing in Adolescent Tibial Shaft Fractures: A Pilot Study

Abstract: Purpose: Elastic stable intramedullary nailing (ESIN) and open reduction internal fixation (ORIF) are literature-supported operative treatments for displaced tibial shaft fractures in skeletally immature patients. Very little is written about rigid intramedullary nails (RIMNs) in adolescents. Our purpose is to describe a physeal-sparing, reamed, locked RIMN technique for adolescent tibial shaft fractures and report its safety. Methods: Adolescent patients with tibial shaft fractures indicated for operative int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…A recent study showed that patients with tibial fractures who weigh 50 kg or less and with proximal tibial growth plates wide open can be treated with elastic stable intramedullary nailing, while more mature adolescents benefit from rigid intramedullary nailing as rigid nailing allows more precise fracture alignment without increased risk of growth disturbance [ 36 ]. Similar findings were observed in another recent study [ 37 ]. Hanf-Osetek et al in their study compared children weighing less than 50 kg or more than 50 kg and found that the use of ESIN in displaced tibial shaft fractures in growing children weighing 50 kg or more is acceptable and safe [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study showed that patients with tibial fractures who weigh 50 kg or less and with proximal tibial growth plates wide open can be treated with elastic stable intramedullary nailing, while more mature adolescents benefit from rigid intramedullary nailing as rigid nailing allows more precise fracture alignment without increased risk of growth disturbance [ 36 ]. Similar findings were observed in another recent study [ 37 ]. Hanf-Osetek et al in their study compared children weighing less than 50 kg or more than 50 kg and found that the use of ESIN in displaced tibial shaft fractures in growing children weighing 50 kg or more is acceptable and safe [ 38 ].…”
Section: Discussionsupporting
confidence: 93%